The need for self-sufficiency and integrated water and energy management: The case study in the water supply system in a small mountain town - Silva, Ana R.C. (2023)
The "Smart energy” concept focuses on (i) being available and accessible in quantity and quality, (ii) being sustainable, that is, economically viable, socially fair, and environmentally correct, and (iii) the 4Es: Energy Amount, being available for consumption; Economic Energy, having viable cost and price; Equity Energy, serving the population with social justice; and Ecologic Energy, not deteriorating nature. Obeying 4Es is demanding, with major stakeholders interacting in the production and consumption policies, and so, the balance between energy and water security within the 4E’s is quite complex, regarding the minimization damage. The main goal of this chapter is to present the results of the EdGeWiSe Project – Energy and Water Systems Integration and Management, which research area focuses on contributing to the integration of water and energy systems in a single and highly efficient system, following the dynamics of the 4Es, specifically, presenting the case study of the development and implementation of a real-scale pilot in an urban context, which took place at Alexandre Aibeo Park, in the mountain city of Covilha, Portugal, considering an integrating water-energy system.